Assessment of bakanae disease response, grain trait associations, and cgSSR based molecular diversity reveal significant variation among rice varieties and breeding lines - Debashis Moharana; Debasis Dash; Anilkumar C; Awadhesh Kumar; Debobrata Dey; Sasmita Behera; Soumya Priyadarsinee Mohanty; C. Mithun; Shyamaranjan Das Mohapatra; Lambodar Behera; Bishnu Charan Marndi; Jeevan B; et al. (Physiological and Molecular Plant Pathology, 2026)

Multi-spectral and multi-platform approaches to space object monitoring: A survey - Mithun Kumar PK; Darryl Ahner (Journal of Space Safety Engineering, 2026)

Cadmium-based coordination polymers as practical luminescent sensors for glutamic acid and Fe3+ in water samples - Jing Luo; Mithun Kumar Ghosh; Yao Xiao; Weiping Wu; Lu Lu; Jiajun Fang; Mohd. Muddassir; Zhenjun Song; Tanmay Kumar Ghorai (Journal of Water Process Engineering, 2026)

Photocatalytic performance of a new Zn(II)-MOF: Structural insights and dye degradation efficiency - Li Yang; Mithun Kumar Ghosh; Xiangxiang Li; Min Xiong; Lu Lu; Tanmay Kumar Ghorai; Mohd. Muddassir; Zhenjun Song; Minle Han (Journal of Water Process Engineering, 2026)

Modelling microplastic fibre emissions from synthetic textiles: An Australian case - Mithun Kumar Biswas; Haiwei Zhou; Liuhua Peng; Wen Li (Journal of Hazardous Materials, 2026)

A modular framework for modeling anthropogenic and environmental trade-offs in sustainable textile material choices - Mir Mohammad Hamza; Mithun Kumar Biswas; K. M. Abdun Noor; Kamruzzaman Sheikh; Rubel Biswas Chowdhury; Mohammad Mosharraf Hossain; Mohammad Sujauddin (Modeling Earth Systems and Environment, 2025)

Preliminary analysis and applications of the Indian Ocean wave drifter program - P. G. Remya; N. Suresh Kumar; Sundhar B. Mithun; B. Praveen Kumar; T. R. Anoop; Venkat Shesu Reddem; C. Jeyakumar; Aneesh A. Lotliker; E. Pattabhi Rama Rao; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2025)
The Southern Ocean (SO) is a critical driver of global wave dynamics, generating long-period swells that propagate vast distances and significantly impact far distant coastal regions, including the Indian coastal regions. Climate change has intensified westerly winds and altered storm tracks in the Southern Hemisphere, resulting in higher wave heights and longer periods, which in turn increase the risk to coastal regions.​ However, the remote and harsh environment in the SO has historically limited in-situ wave observations, hindering a comprehensive understanding of the wave characteristics in the region. To bridge this gap, the Indian National Centre for Ocean Information Services (INCOIS) launched the Indian Ocean Wave Drifter (IOWD) program in 2021 under the Deep Ocean Mission to address the in-situ data gap in the Southern Indian Ocean. Through the deployment of GPS-enabled directional wave spectra drifters, the program has enabled near-real-time observations of wave characteristics across the SO. This article highlights the early outcomes of the IOWD program, including wave model validation, Stokes drift estimation, and swell tracking. The study emphasizes the importance of sustained in-situ observations from remote oceans for improving wave forecasting, enhancing coastal preparedness, and advancing scientific understanding of wave–current interactions and climate variability in the Indian Ocean region.

Anti-Parkinson potential of hesperetin nanoparticles: in vivo and in silico investigations - Praveen Kumar Pasala; Prasanth DSNBK; Mithun Rudrapal; Ranadheer Reddy Challa; Sheikh F. Ahmad; Bhaskar Vallamkonda; Ram Babu R. (Natural Product Research, 2025)

Machine learning assisted Raman spectroscopy: A viable approach for the detection of microplastics - Megha Sunil; Nazreen Pallikkavaliyaveetil; MIthun. N; Anu Gopinath; Santhosh Chidangil; Satheesh Kumar; Jijo Lukose (Journal of Water Process Engineering, 2024)

Visualization and characterisation of microplastics in aquatic environment using a home-built micro-Raman spectroscopic set up - Megha Sunil; Mithun N; Meril Charles; Santhosh Chidangil; Satheesh Kumar; Jijo Lukose (Journal of Environmental Management, 2024)

Navigating Sustainability through Greenhouse Gas Emission Inventory: ESG Practices and Energy Shift in Bangladesh’s Textile and Readymade Garment Industries - Mithun Kumar Biswas; Abul Kalam Azad; Anupa Datta; Shuvasish Dutta; Shimul Roy; Shauhrat S. Chopra (Environmental Pollution, 2024)

Hydrophilic polydopamine/polyvinylpyrrolidone blended polyphenylsulfone hollow fiber membranes for the removal of arsenic-V from water - Mithun Kumar; Arun M. Isloor; M.C.S. Nayak; Somasekhara Rao Todeti; Mahesh Padaki; Ahmad Fauzi Ismail (Journal of Environmental Chemical Engineering, 2023)

3-(Bromoacetyl) coumarin is a potential therapeutic agent against neonatal sepsis-associated Pseudomonas extremorientalis - Shukla Banerjee; Sukesh Kumar Bajire; H. K. Mithun; Rajesh P. Shastry (Archives of Microbiology, 2023)

Taking stock of the share of global environmental burden of knitwear production in Bangladesh: Constructing the life cycle inventory - Md Asef Al Alam; Mithun Kumar Biswas; Tashfia Mahiat; Rubel Biswas Chowdhury; Karabi Farhana Biswas; Mohammad Mosharraf Hossain; Mohammad Sujauddin (Journal of Cleaner Production, 2023)

Raman spectroscopy for viral diagnostics - Jijo Lukose; Ajaya Kumar Barik; Mithun N; Sanoop Pavithran M; Sajan D. George; V. M. Murukeshan; Santhosh Chidangil (Biophysical Reviews, 2023)
Raman spectroscopy offers the potential for fingerprinting biological molecules at ultra-low concentration and therefore has potential for the detection of viruses. Here we review various Raman techniques employed for the investigation of viruses. Different Raman techniques are discussed including conventional Raman spectroscopy, surface-enhanced Raman spectroscopy, Raman tweezer, tip-enhanced Raman Spectroscopy, and coherent anti-Stokes Raman scattering. Surface-enhanced Raman scattering can play an essential role in viral detection by multiplexing nanotechnology, microfluidics, and machine learning for ensuring spectral reproducibility and efficient workflow in sample processing and detection. The application of these techniques to diagnose the SARS-CoV-2 virus is also reviewed. Graphical abstract

Characterizing ocean surface contamination: Composition, film thickness, and rheology - B. Mithun Sundhar; Girish Kumar Rajan (Marine Pollution Bulletin, 2023)

Photonics of human saliva: potential optical methods for the screening of abnormal health conditions and infections - Jijo Lukose; Sanoop Pavithran M.; Mithun N.; Ajaya Kumar Barik; Keerthilatha M. Pai; V. K. Unnikrishnan; Sajan D. George; V. B. Kartha; Santhosh Chidangil (Biophysical Reviews, 2021)
Human saliva can be treated as a pool of biological markers able to reflect on the state of personal health. Recent years have witnessed an increase in the use of optical devices for the analysis of body fluids. Several groups have carried out studies investigating the potential of saliva as a non-invasive and reliable clinical specimen for use in medical diagnostics. This brief review aims to highlight the optical technologies, mainly surface plasmon resonance (SPR), Raman, and Fourier transform infrared (FTIR) spectroscopy, which are being used for the probing of saliva for diverse biomedical applications. Advances in bio photonics offer the promise of unambiguous, objective and fast detection of abnormal health conditions and viral infections (such as COVID-19) from the analysis of saliva.

Monitoring forest landcover changes in the Eastern Sundarban of Bangladesh from 1989 to 2019 - Mithun Kumar; Ismail Mondal; Quoc Bao Pham (Acta Geophysica, 2021)

Evaluation of Tomato Inbred Lines Harboring Ty Gene(s) for Resistance Against Monopartite and Bipartite Begomoviruses - Pardhasaradhi Prabhandakavi; Rakesh Kumar; Santanu Acharya; Mithun Chakraborty; P. Rambabu; Sairam Reddy Palicherla; Rajasekhar Pinnamaneni (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Improved separation of dyes and proteins using membranes made of polyphenylsulfone/cellulose acetate or acetate phthalate - Mithun Kumar; Arun M. Isloor; Somasekhara Rao Todeti; G. P. Syed Ibrahim; Inamuddin; Ahmed Fauzi Ismail; Abdullah M. Asiri (Environmental Chemistry Letters, 2020)

New Record of Equisetum ramosissimum subsp. debile from Lower Gangetic Plain, West Bengal, India and Conservation Approach - Mithun Biswas; Aninda Mandal; Madhuparna Hore; Subikash Biswas; Suvendu Dey; Jayita Biswas; Amrik Mondal; Bidyut Kumar Mandal; Piu Das; Sudha Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)